Tillandsia itatiensis: a new species of Tillandsia L. (Bromeliaceae) from Bahia, Brazil - Leodegario, Marcio De Melo; Cavalcante, Brayan Paiva; Aona, Lidyanne Yuriko Saleme; Wanderley, Maria Das Graças Lapa; Souza, Everton Hilo De (Phytotaxa, 2020)
The authors describe, discuss, and illustrate Tillandsia itatiensis, a new species from the Caatinga biome in the municipality of Itatim, Bahia, Brazil. The new species is similar to T. streptocarpa and T. grao-mogolensis, regarding morphological characters such as caulescent habit, curved stem, simple inflorescence with no more than five flowers per inflorescence and simple-erect stigma. It inhabits inselbergs in Caatinga forest, where it is critically endangered (CR) due its small distribution and human extractivism.